The intersection of the interior in Sadr City, Baghdad Problems and solutions Studies in transportation geography - Arma, Nadia Muttlaq (Technium Social Sciences Journal, 2022)
Traffic jams have become a phenomenon that all areas of Baghdad suffer from in general and the study area in particular, as it is characterized by a very high population density, as its population (Al-Sadr City is 5 million people), this percentage is very high and the various activities that it entails, whether at the commercial, governmental, educational or health levels, and the movement of those activities requires movement It reflects the daily traffic volume of the roads in it, which creates a stifling problem, or traffic jams, if the roads and intersections do not accommodate the volumes of traffic passing by.Proceeding from the plan of the Municipality of Baghdad to improve the performance of the transport network in Baghdad and make this network comparable to its counterparts in the capitals of developed countries, by converting most of the main intersections in Baghdad into bridges to ensure the continuity of the drainage of traffic volumes and reduce the use of traffic lights. Therefore, the Municipality of Baghdad contracted with The competent authorities to implement a bridge intersection in Sadr City for the intersection of Al-Dakhil Street with Al-Quds Street instead of the current intersection, which suffers from severe traffic jams, if the service level is less than F, which is the worst level of service. Which represents the subject of the research, which is concerned with studying the intersection in terms of its importance, its geographical location, traffic volumes, determining the peak hours, conducting an analysis of the current operating conditions, and finding future volumes for the design period of the proposed bridge, which is the target year 2030.